Tax Avoidance Terhadap Perspektif Komisaris Independen,Kompensasi Rugi Fiskal dan Pertumbuahn Aset - Siti Zulfatin Nihayah; Rachmawati Meita Oktaviani (Politeknik Ganesha Medan, 2022)
Tax avoidance is a tax avoidance practice carried out by taxpayers, especially corporate taxpayers to reduce or even eliminate the tax burden by taking advantage of loopholes. In tax policies and regulations. This study aims to analyze and examine the effect of independent commissioners, asset growth and fiscal loss compensation on tax avoidance. The population used in this study are mining sector companies listed on the Indonesia Stock Exchange (IDX) for a five-year period, 2016-2020. With a final sample of 60. The method used in this research is using purposive sampling technique. The data analysis technique uses panel data regression analysis using the Eviews 12 program. The results of this study partially explain that independent commissioners have a significant negative effect on tax avoidance, asset growth has no significant effect on tax avoidance. And fiscal loss compensation has no significant effect on tax avoidance.